Analisa Jaringan Pipa Distribusi Air Bersih Kecamatan Kerinci Kanan (Studi Kasus: Kecamtan Kerinci Kanan, Kabupaten Siak) - Pandu Hudiiasto; Siswanto Siswanto; Trimaijon Trimaijon (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The area to be reviewed in this writing is a district located in Riau Province, namely Kerinci Kanan District. Kerinci area Right water is difficult due to its location far from the water source and the soil is not safe to be drilled. Previous drilling efforts have been made for the wellbore, but from inside the soil emit a kind of gas odor so that drilling is stopped. The Local Government has built a Water Treatment Plant (WTP) located in Lubuk Dalam District to meet the needs of clean water in Lubuk Dalam District and Kerinci Kanan District. For water sources taken from Buatan River. Distribution pipes are still in progress and need testing in software or lab tests. This test aims to ensure that the water discharged can meet the needs of the community as planned.Keywords: EPANET 2.0, distribution pipes, clean water.